2012
DOI: 10.1039/c1sm06623d
|View full text |Cite
|
Sign up to set email alerts
|

From highly ramified, large scale dendrite patterns of drying “alginate/Au NPs” solutions to capillary fabrication of lab-scale composite hydrogel microfibers

Abstract: The processes of complexation, aggregation and self-assembly involving natural polymers are not only ubiquitous in biological systems (proteins), but they are also crucial for environmental and technological applications (humic acids, polysaccharide-based hydrogels). In this paper, we address these issues through a model study of the drying structures of bi-component solutions of oppositely charged alginate polysaccharide and gold nanoparticles. Unlike single component alginate and nanoparticle solutions, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The bio-fluid compounds usually contain dissolved salt in them, and the deposition patterns of these salt-protein biofluid droplets were reported [52,53,54] . The formation of dendritic patterns was shown by Darwich et al [55] for a bi-component solution of oppositely charged alginate polysaccharides and gold nanoparticles. The dendritic structure formation was dependent on the salt concentration, drying mode, and particle size.…”
Section: Introductionmentioning
confidence: 77%
“…The bio-fluid compounds usually contain dissolved salt in them, and the deposition patterns of these salt-protein biofluid droplets were reported [52,53,54] . The formation of dendritic patterns was shown by Darwich et al [55] for a bi-component solution of oppositely charged alginate polysaccharides and gold nanoparticles. The dendritic structure formation was dependent on the salt concentration, drying mode, and particle size.…”
Section: Introductionmentioning
confidence: 77%
“…This complexity is enhanced by the multi-phase nature of the material: liquid menisci between particles generate heterogeneous shrinkage through capillary pressure, and excess liquid-vapor surface area in the bulk of the material [32][33][34][35][36]. As a consequence, in addition to polygonal cracks, a large variety of cracks patterns have been reported in dried suspensions [8,30,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52]. The variability in observed patterns depends on numerous factors such as film geometry [40,53], particle mechanics [54], liquid additives [55,56], preparation history [57,58], solvent volatility [59,60], and external fields [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…Hierarchical architectures self-organized from artificial nanoscale building blocks have attracted much attention due to their fascinating optical, electronic, sensing, and catalytic properties. Hierarchical architectures of metals, oxides, sulfides, carbonates, biomolecules, or organic–inorganic hybrid materials have been realized and are generally formed in specifically tailored chemical or electrochemical systems. However, it remains a challenge to develop a simple synthetic approach to create morphology-controlled hierarchical architectures of various systems. Hierarchical architectures can also be formed in aqueous solutions or in gels under appropriate physical conditions, including the evaporation rate, temperature, pressure, viscosity, and concentration. It has been demonstrated that polymers, semicrystalline polymers, and biomolecules, such as silk proteins, alginate polysaccharides, and actin filaments, can themselves, or in interaction with other components such as gold nanoparticles, form hierarchical structures. Nonetheless, the degree of branching and angles between branches are often arbitrary and of little control due to random aggregation, making pattern prediction difficult and, hence, limiting certain applications of such structures. In addition, biomaterials are not easily applied to conventional fabrication processes due to their easy degradation in nonaqueous environments.…”
mentioning
confidence: 99%